Minimum Wage, Inflation, Interest Rate and Household Consumption In Indonesia - Putri Valentine; Sabilayana Sabilayana; Andria Zulfa; Lia Nazliana Nasution; Dwita Sakuntala (Jurnal Telekomunikasi dan Informatika, 2024)
This study aims to determine the effect of minimum wages, inflation, and lending rates on household consumption in Indonesia. The variables in this study are minimum wage, inflation, and lending rates as independent variables, while the household consumption variable is the dependent variable. The research period is from 1993-2023. The data analysis technique used is the Autoregressive Distributed Lag (ARDL) panel. The results of this study indicate that the province that is able to become a leading indicator for the stability of household consumption is North Sumatra. When viewed from the short run and long run, the Minimum Wage variable has an insignificant effect on Household Consumption in the short term but has a significant effect on Household Consumption in the long term. Inflation variable has a significant effect on Household Consumption in the short run, while in the long run Inflation variable has an insignificant effect on Household Consumption. The loan interest rate variable has no significant effect on household consumption in the short term or in the long term.